Análisis de la tecnología ORM-HIBERNATE con respecto a la productividad, aplicado al sistema de gestión de documentación del departamento de procuraduría de la UNACH. - Tixi Cuzco, Ismael Franklin (2016)
The main objective of this Thesis is to research technology-Hibernate ORM. With respect to productivity focused on data access and expose their main concepts, features, services and performance, for the development of Document Management System for the Department of Attorney General of the National University of Chimborazo. This research has four chapters. Chapter I begins with a framework, followed by the objectives and proper justification of this study. In Chapter II is theoretically supports this work with all the necessary information and complementary where the main concepts and features of the ORM-Hibernate technology and development architecture N-tier shown. Chapter III develops comparative analysis of architecture N-tier development and technology-Hibernate ORM concerning productivity focused data access and surveys of experts in the development of web applications to meet the objectives of the investigation. Chapter IV Management System Documentation is developed by applying the Hibernate ORM-tech, development methodology using XP in phases of planning, design, coding and testing. Management System Documentation for the Department of Attorney General developed UNACH where information about processes trades, agreements, contracts and trials had adequate and transparent organization. Furthermore, the development of this application is a project of the Attorney General registered in the UPR system of the National University of Chimborazo.